Test on Compaction Reinforcement Effect of Sand - Lianzhen Zhang; Qingsong Zhang; Zhipeng Li; Hongbo Wang (Advances in Materials Science and Engineering)
In fracture or compaction grouting projects of sand layer, there exist many compacted sand regions on both sides of grout veins or around grout bulbs. It has an important effect on the final reinforcement effect of the sand layer that how much performance of the sand layer is improved after being compacted. Compression modulus, cohesion, and permeability coefficient are selected to be the performance indexes of the compaction reinforcement effect of sand. The relationship between the performance properties of sand and grouting pressure has been tested and analyzed. And influences of clay content and initial water ratio of sand on the compaction reinforcement effect have been studied. Results show that compaction can effectively improve the mechanical properties and impermeability properties of sand. Compression modulus of sand increases by 2∼18 times. The cohesion of sand increases from the scope of 9.4∼26 kPa to the scope of 40∼113.6 kPa. The permeability coefficient of sand decreases from the scope of 1.0 × 10−2∼ 8.33 × 10−4 cm/s to the scope of 2.19 × 10−4∼2.77 × 10−9 cm/s. When the clay content of sand is smaller than about 20%, sand cannot be reinforced effectively by compaction. Cohesion cannot be improved significantly and the permeability coefficient cannot be reduced markedly. A high initial water ratio of sand is beneficial to improve the compression modulus of compacted sand and goes against the improvement of cohesion of compacted sand. In addition, the initial water ratio has little effect on the permeability coefficient of compacted sand. In the end, fitting formulas have been developed to quantitatively describe the compaction reinforcement effect of sand by different grouting pressures.